Pelestarian Varietas Padi Ladang Lokal untuk Pertanian Berkelanjutan: Pelestarian Varietas Padi Lokal Bangka - Nopriansyah, Syarli; Mustikarini, Eries Dyah; Khodijah, Nyayu Siti (Universitas Galuh, 2024)
One of the biggest staple foods for the Indonesian population is rice which comes from the rice plant commodity. Food needs are increasing in line with the rate of population growth. Increasing rice production does not have to be done through paddy fields, but new breakthroughs must be made, namely by utilizing marginal land to be converted into potential land. The rice fields planted and developed by Bangka farmers are local varieties that have adapted to the local environment. This local variety, which is developed and planted continuously, has not been released nationally, so the seeds produced are not labeled seeds. The aim of this research is to preserve and promote the existence of local rice varieties that have advantages so that they can be widely developed by becoming local superior seeds that are labeled and certified. This research uses qualitative and descriptive methods with the process of collecting primary and secondary data, in the form of direct interviews with farmers in Tiang Tara Village, Mendo Village and Labuh Air Pandan Village and collecting data from the field. The data analysis used in determining the strategy is SWOT analysis, so as to obtain a strategy for developing local rice farming in Bangka Regency. The conclusions obtained were to preserve and promote the existence of local rice varieties, strategies and breakthroughs were carried out by 1) Registering local varieties at the Center for Plant Variety Protection and Agricultural Licensing (PPVTPP); 2) Encourage and maintain the community to continue cultivating local rice; 3) Collaborating with the Ministry of Agriculture's BSIP to release local rice varieties; 4) Provide guidance and assistance to farmers to implement Good Agricultural Practices (GAP); 5) Initiate planting more than one season per year; 6) Establish the LP2B Regional Regulation (Sustainable Food Farming Land); 7) Release local rice varieties that have advantages